Development of Learning Media Using VideoScribe for the Subject of Present Continuous Tense - Pahmi; Wandi Syahfutra (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2019)
To master English, students must learn many things, including about grammar in order to use English properly and correctly. There are a number of ways lecturers can do to support teaching and learning process, one of which is by making use of technology to develop learning media. Using media is expected to make learning process about grammar enjoyable. This research aims to develop learning media using VideoScribe for the subject of Present Continuous Tense which is one of the materials studied by odd semester students at Universitas Muhammadiyah Riau. This research further designs, implements and tests the feasibility of the learning media. This research is a research and development (R&D) model with ADDIE which consists of 5 stages, namely Analysis, Design, Development, Implementation and Evaluation. The subjects of this study were undergraduate students majoring in non-English Department which consisted of 35 students in odd semester. The results of alpha testing, expert material assessment showed that the media that were designed was in a very good category with an average score of 4.26. Meanwhile, for trials with students, the video animation media using VideoScribe was in a very good category with an average score of 4.25. Therefore, it can be concluded that the instructional media designed is suitable to be used to support teaching and learning activities.